Multi‐phase extraction of ephedrine from Pinellia ternata and herbal medicine using molecular imprinted polymer coated ionic liquid‐based silica. Issue 2 (21st August 2019) - Fang, Luwei; Xie, Jinfeng; Lin, Liangwen; Tian, Minglei; Row, Kyung Ho
Abstract: Introduction: Ephedrine is a typical compound found in lots of plant species that is used in several medicines for the treatment of asthma and bronchitis. However, excess amounts are harmful to humans, so it needs to be removed. Objective: This study developed a multi‐phase extraction (MPE) method with a molecular imprinted polymer (MIP) coated ionic liquid (IL)‐based silica (SiO2 @IL@MIP) to simultaneously extract and separate ephedrine from Pinellia ternata, 10 medicines, and urine samples. Methods: IL was immobilized on silica. Subsequently, the IL was combined with the functional monomer, followed by the addition of the crosslinker and template. The resulting sorbent was applied to the MPE, and the extraction, washing and elution solvents were evaluated. Results: Fourier‐transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) confirmed the synthesis of SiO2 @IL@MIP. A maximum adsorption amount of 5.76 mg/g was obtained at 30°C at a neutral pH. In MPE, 10.00 mL of methanol could extract all the ephedrine from Pinellia ternata . The interference was removed by washing with 4.00 mL of water, ethanol, and acetonitrile. Finally, 8.00 mL of methanol/acetic acid (99:1, v / v ) was applied as the elution solvent. The following were extracted: 5.50 μg/g of ephedrine from Pinellia ternata, 0.00–46.50 μg/g from the 10 herbal medicines, and 68.70–102.80 μg/mL in the urine samples. Conclusion: The proposed method was applied successfully to the simultaneously extraction and separation of ephedrine from plants and medicines. These results are expected to provide important data for the development of new methods for the separation and purification of bioactive compounds. Abstract : A multiphase extraction (MPE) method with a molecular imprinted polymer coated ionic liquid‐based silica to simultaneously extract and separate ephedrine from real samples. In MPE, methanol could extract all the ephedrine. The interference can be removed by water, ethanol, and acetonitrile. Methanol/acetic acid was applied as the elution solvent. Finally, the MPE method isolated 5.50 μg/g of ephedrine from Pinellia ternata, 0.00–46.50 μg/g from the ten herbal medicines, and 68.70–102.80 μg/mL in the urine samples.